2018
DOI: 10.5056/jnm17059
|View full text |Cite
|
Sign up to set email alerts
|

Is It Useful to Administer Probiotics Together With Proton Pump Inhibitors in Children With Gastroesophageal Reflux?

Abstract: Background/Aims Gastroesophageal reflux disease (GERD) is a frequent condition diagnosed in children and treated with proton pump inhibitors (PPI). Long-term PPI administration can alter intestinal bacterial population by suppressing the gastric acid barrier and may cause diarrhea. The aim of this study is to evaluate the prevalence of small intestinal bacterial overgrowth assessed by glucose hydrogen breath test among children that received 12 weeks of PPI with or without probiotics ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…So far only one small study addressed the effect of probiotics in children receiving a 12 week treatment with PPI for gastroesophageal reflux. In this study no microbiome sequencing data were presented, but small intestinal bacterial overgrowth (measured with a hydrogen breath test) could be reduced significantly 24 .…”
Section: Discussionmentioning
confidence: 97%
“…So far only one small study addressed the effect of probiotics in children receiving a 12 week treatment with PPI for gastroesophageal reflux. In this study no microbiome sequencing data were presented, but small intestinal bacterial overgrowth (measured with a hydrogen breath test) could be reduced significantly 24 .…”
Section: Discussionmentioning
confidence: 97%
“…After 12 weeks of treatment with a proton pump inhibitor, dysbiosis was diagnosed according to the results of a glucose hydrogen breath test in 56.2% of the children in the placebo group, compared to 6.2% of the children in the probiotic group (P < 0.001) [72]. Bacterial overgrowth was detected in 5% of controls, which is similar to the group treated with L. reuteri and proton pump inhibitors [72].…”
Section: Probiotics and Prevention Of Regurgitationmentioning
confidence: 73%
“…In a clinical study on patients with functional dyspepsia, Tsuda et al[25] found that 4 wk of PPI use caused SIBO. Oana et al[26] conducted a clinical trial on pediatric gastroesophageal reflux disease (GERD) patients administered probiotics and PPI for 12 wk and found that probiotics administration decreased the rate of dysbiosis in children treated with PPI. Jacobs C et al[27] conducted a study focusing on the risk factors of SIBO.…”
Section: Discussionmentioning
confidence: 99%